Constructions of 2-D Golay Complementary Array Sets With Flexible Array Sizes for Omnidirectional Precoding in Massive MIMO - Men, Xinyu; Liu, Tao; Li, Yubo; Liu, Mingxin (IEEE communications letters, 2023)
Constructing two-dimensional (2-D) Golay complementary array sets (GCASs) with flexible array sizes become an important topic due to their practical application for omnidirectional precoding in massive multi-input multi-output (MIMO) systems. In this letter, we propose two direct constructions of GCASs from 2-D extended generalized Boolean functions (EGBFs). Compared with the previous works, the presented constructions lead to more flexible array sizes for a fixed set size, which may give an extra benefit in accommodating more URA configurations. Simulation results indicate that the proposed GCASs can be employed as precoding matrices to achieve omnidirectional transmission, and behave a superior bit error rate (BER) performance over other schemes.